Human capital development and economic growth in Nigeria: a structural break perspective - Adebayo, Moses; Oloke, Olufunnso O; Usman, Owolabi A (International Journal of Finance Research, 2023)
The study examined human capital development and economic growth in Nigeria using secondary data obtained from CBN statistical bulletin for the period of forty years between 1981-2020. Agriculture (AGR), Civil-Service (CIVSER), Education (EDU), Health (HLTH), Manufacturing (MANU) and Transportation (TRANSP) sectors of Nigerian economy were used from 1981 to 2020 as proxies for expenditure on human capital development and independent variables for the studies while Gross Domestic Product (GDP) was used as proxy for economic growth and the dependent variable. Structural break analysis was used which shows no structural break occurrence in Nigeria within the period of study. It could also be seen that expenditure on human capital development on civil servants, education, manufacturing and health were found significant with exception of agriculture and transportation that were not significant in the least square results generated with the structural break analysis. Generally, with the R-squared and Adjusted R-squared of 96% and 95% respectively, it could be submitted that for forty years under consideration, there is smooth correlation between human capital development and economic growth in Nigeria. The Structural Adjustment Program (SAP) that was introduced in July 1986 and lasted till June 1998 was not strong enough to influence human capital development and economic growth. This was supported by the structural break graph and cusum graph.